2017
DOI: 10.1111/asej.12117
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Reverse Mortgage Option in Hong Kong

Abstract: The reverse mortgage is a very useful financial product for senior citizens who own homes but do not have a cash income, while it is a high-risk product from the lender's perspective. One of benefits of reverse mortgages is that the debt limit is restricted to the scope of the disposition price of the collateralized house, which is considered a put option to borrowers. The present study evaluates the option value of the reverse mortgage in Hong Kong through an empirical analysis using the Black-Scholes option-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 23 publications
1
14
0
Order By: Relevance
“…According to Pu et al (2014), Tsay et al (2014) and Han et al (2017), if changes in housing prices follow the log-normal random walk form, the present value of redemption option true( V T a true) is the value of the European call option, which can be estimated based on the B ~ S option pricing model. Therefore, we can calculate the logarithmic house price growth rate based on the historical data of the real-estate market and then perform a normal distribution fitting to verify whether the historical house price obeys log-normal distribution.…”
Section: Theoretical Model and Research Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Pu et al (2014), Tsay et al (2014) and Han et al (2017), if changes in housing prices follow the log-normal random walk form, the present value of redemption option true( V T a true) is the value of the European call option, which can be estimated based on the B ~ S option pricing model. Therefore, we can calculate the logarithmic house price growth rate based on the historical data of the real-estate market and then perform a normal distribution fitting to verify whether the historical house price obeys log-normal distribution.…”
Section: Theoretical Model and Research Methodsmentioning
confidence: 99%
“…Currently, little quantitative research has been done on the economic validity of HRM with redemption right. In addition, according to the characteristics of Hong Kong’s RMP, Han et al (2017) has confirmed the value of the redemption option and argued that the HRM with redemption option implies European call option, and that the elderly (or his or her heir) can obtain the option value. However, Han’s study confirmed only the option value of the redemption right and did not further analyze the economic validity of the elderly’s participation in HRM with redemption right.…”
Section: Literature Reviewmentioning
confidence: 96%
“…With reverse mortgages, the older homeowners may borrow from the lenders using their properties as collateral. The borrowers may choose to take the funds either as fixed monthly instalments in the form of pensions, line of credit, or lump sums (Han et al, 2017). Hence, reverse mortgages have been an important financial tool for cash-poor seniors to release home equity (Shi and Lee, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Reverse mortgages (RM) can effectively integrate the comprehensive advantages of the real estate, pension insurance, and financial markets, as well as allow the houses owned by the elderly to serve in three ways: (i) for habitation; (ii) to provide shelter for the elderly; and (iii) for investment. These functions represent a beneficial supplement to traditional old‐age security (Han et al ., 2017). With the rapid development of the real estate market in China, the large proportion of residential houses, and the gradual rise of urbanization, the development of reverse mortgages can transform social housing assets into pension resources.…”
Section: Introductionmentioning
confidence: 99%